Detoxification of Heavy Metals - Sherameti, Irena; Varma, Ajit.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Heavy metals are severe environmental pollutants, and many of them are toxic even at very low concentrations. With industrial development, soil pollution with heavy metal elements have dramatically increased. The uptake of heavy metals via plants that are exposed to contaminated soils is a risk for human health and a major hazard for the ecosystem as a whole, including soil microorganisms. On the other hand, plants may be used in the decontamination of soils. The topics presented in this book include: sources of heavy metals contaminants in soils; plant species that can grow on contaminated soils; the phytoremediation of contaminated soils; tolerance, accumulation and detoxification mechanisms of zinc, copper, arsenic, cadmium and vanadium in plants; the critical role of sulfur metabolism in heavy metal tolerance; the role of aquatic macrophytes, plant growth-promoting bacteria, sugar crops and earthworms in detoxification; and heavy metal stabilization by promoting zeolite synthesis in soils.
Detoxification of Heavy Metals: State of Art -- Plants in Heavy Metal Soils -- Functional Significance of Metal Ligands in Hyperaccumulating Plants: What do We Know? -- Progress in Phytoremidiating Heavy-metal Contaminated Soils -- Plant Taxonomy and Metal Phytoremediation -- Reclamation of Contaminated Mine Ponds using Marble Wastes, Organic Amendments and Phytoremediation -- The Role of Membrane Transport in the Detoxification and Accumulation of Zinc in Plants -- Initial Steps of Copper Detoxification: Outside and Inside of the Plant Cell -- Arsenic Tolerance and Detoxification Mechanisms in Plants -- Cadmium Metal Detoxification and Hyperaccumulators -- Transport, Accumulation and Physiological Effects of Vanadium -- Microbial Remediation of Arsenic Contaminated Soil -- Fate of Cadmium in Calcareous Soils under Salinity Conditions -- Organellar Proteomics: A High-Throughput Approach for Obtaining a better Understanding of Heavy Metal Accumulation and Detoxification in Plants -- Sulfur Metabolism as a Support System for Plant Heavy Metal Tolerance -- Cd(II)-activated Synthesis of Phytochelatins -- Tolerance, Accumulation and Detoxification Mechanism of Copper in Elsholtzia splendens -- Role of Aquatic Macrophytes in Biogeochemical Cycling of Heavy Metals - Relevance to Soil - Sediment Continuum Detoxification and Ecosystem Health -- Role of Plant Growth Promoting Bacteria and Fungi in Heavy Metal Detoxification -- Detoxification of Heavy Metals From Soils Through Sugar Crops -- Detoxification of Heavy Metals Using Earthworms -- Heavy Metal Stabilization by Promoting Zeolite Synthesis in Soil.
Keywords: Life sciences; Biochemistry; Plant physiology; Soil conservation; Life Sciences; Plant Physiology; Plant Biochemistry; Soil Science & Conservation